Novel lnc RNA regulated by HIF‐1 inhibits apoptotic cell death in the renal tubular epithelial cells under hypoxia. Issue 8 (18th April 2017) - Mimura, Imari; Hirakawa, Yosuke; Kanki, Yasuharu; Kushida, Natsuki; Nakaki, Ryo; Suzuki, Yutaka; Tanaka, Tetsuhiro; Aburatani, Hiroyuki; Nangaku, Masaomi
Abstract: Chronic tubulointerstitial hypoxia plays an important role as the final common pathway to end‐stage renal disease. HIF‐1 (hypoxia‐inducible factor‐1) is a master transcriptional factor under hypoxia, regulating downstream target genes. Genome‐wide analysis of HIF‐1 binding sites using high‐throughput sequencers has clarified various kinds of downstream targets and made it possible to demonstrate the novel roles of HIF‐1. Our aim of this study is to identify novel HIF‐1 downstream epigenetic targets which may play important roles in the kidney. Immortalized tubular cell lines (HK2; human kidney‐2) and primary cultured cells (RPTEC; renal proximal tubular cell lines) were exposed to 1% hypoxia for 24–72 h. We performed RNA‐seq to clarify the expression of mRNA and long non‐coding RNA (lncRNA). We also examined ChIP‐seq to identify HIF‐1 binding sites under hypoxia. RNA‐seq identified 44 lncRNAs which are up‐regulated under hypoxic condition in both cells. ChIP‐seq analysis demonstrated that HIF‐1 also binds to the lncRNAs under hypoxia. The expression of novel lncRNA, DARS‐AS1 (aspartyl‐tRNA synthetase anti‐sense 1), is up‐regulated only under hypoxia and HIF‐1 binds to its promoter region, which includes two hypoxia‐responsive elements. Its expression is also up‐regulated with cobalt chloride exposure, while it is not under hypoxia when HIF‐1 is knocked down by siRNA. To clarify the biological roles of DARS‐AS1, we measured the activity of caspase 3/7 using anti‐sense oligo of DARS‐AS1. Knockdown of DARS‐AS1 deteriorated apoptotic cell death. In conclusion, we identified the novel lncRNAs regulated by HIF‐1 under hypoxia and clarified that DARS‐AS1 plays an important role in inhibiting apoptotic cell death in renal tubular cells. Abstract : We identified a novel lncRNA named DARS‐AS1 regulated by HIF‐1 under hypoxia using renal tubular cells. We clarified that DARS‐AS1 plays an important role in inhibiting apoptotic cell death under hypoxic condition.